Enigmatic clastic pipe swarms and implications for fluidization dynamics in aeolian deposits. Issue 2 (16th July 2018) - Chan, Marjorie A.; Hasiotis, Stephen T.; Parrish, Judith T.
Abstract: Soft‐sediment deformation of contorted and massive sandstone is common throughout much of the siliciclastic record, but clastic pipes represent a distinctive class of pressurized synsedimentary features. Remarkable centimetre to metre‐scale clastic pipe exposures in the Jurassic Navajo Sandstone of Utah (USA) establish a range of pipe sizes, expressions and relationships to the host rock in an erg margin setting, traditionally thought to be just a dry desert system. In particular, the field and laboratory characterizations of cylindrical pipes show internal concentric, annular rings that imply water fluidization, with alignment of long grain axes due to shear flow along pipe margins. Central interior parts of decimetre‐scale pipes appear massive in plan view, but display weakly developed pseudobedding from post‐pressure release, gravitational settling in the cross‐sectional view. Deformation features of conjugate fractures, ring faults, hypotrochoid patterns (geometric arcs and circles) and breccia in the host material reflect both brittle and ductile behaviour in response to the fluidization and injection of the clastic pipes. The stratigraphic context of individual pipes and the stratabound intervals of pipe features imply dynamic deformation nearly coincident with deposition in this Early Jurassic aeolian system related to multiple factors of groundwater expulsion, timing and local host sediment properties that influenced pipe development. Although the pipe features might be easily overlooked as a smaller scale feature of soft‐sediment deformation in dune deposits, these are valuable environmental indications of disrupted fluid pathways within porous, reservoir quality sands, associated with possible combinations of periodic springs, high water‐table conditions and strong ground‐motion events. These pipe examples may be important analogues where exposures are not so clear, with applications to diverse modern and ancient clastic settings internationally on Earth as well as in planetary explorations such as on Mars.